Successful Regional Anesthetic for a Parturient with Moyamoya Syndrome - Anjalena Pasam (Case Reports in Anesthesiology, 2020)
Anesthesia for Cesarean section could be challenging due to the physiological changes during pregnancy, but it can be more complicated if associated with sickle cell disease and moyamoya disease. The moyamoya syndrome is nothing but sickle cell disease complicated by cerebral vasculopathy. Incidence of moyamoya disease in the USA is 0.086/100,000 people. We report a case of a pregnant woman with sickle cell disease and moyamoya syndrome, who underwent a successful spinal epidural for primary cesarean section, with careful monitoring of blood pressure.